B12 Sex differences of 12 lead electrocardiographic findings of the rugby football league athlete - Warrington, Callum; Cooper, Rob; George, Keith; Mill, Nathan; Thompson, Andy; Read, Jade; Abram, Jonathan; Oxborough, David (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
Cardiac electrical adaptations occur within athlete populations. Sex-related variations in the normal athlete electrocardiogram (ECG) have been observed, with males exhibiting increased QRS and PR intervals, while females have demonstrated increased QTc intervals in university-level athletes. Male athletes also maintain greater weekly training hours compared to female athletes, which is associated with increased ECG changes. The presence of these differences within Rugby Football League (RFL) athletes is unknown. This study aimed to investigate any sex-related variations in the 12-lead ECG in RFL athletes. Fifty nine RFL athletes (32 males [age = 25 ± 5 years] and 27 females [age = 24 ± 5 years]) were included in the study. One female was excluded with inferior T wave inversion and was referred for further investigation. The 12-lead ECG was collected as part of the athlete’s pre-season cardiac screening alongside completion of a health questionnaire, assessment of height and weight and brachial artery pressure. Continuous variables (i.e. heart rate, PR interval, QRS interval etc.), were analysed using an independent t-test or a Mann-Whitney U test as appropriate. For assessment of nominal data (i.e. incidence of early repolarisation and junctional rhythm etc.) a chi-squared test or Fishers exact test were used. A Spearman’s correlation coefficient was used to determine any association between training hours and ECG findings. Ethics approval was obtained from Liverpool John Moores University Ethics Committee. Height (183 ± 5 vs. 169 ± 5 cm, P <0.001), weight (95 ± 11 vs. 77 ± 11 kg, P <0.001) and weekly training hours (18 ± 5 vs. 12 ± 5 hrs, P = 0.001) were higher in male athletes. PR interval (156 ± 34 vs. 142 ± 19 ms, P = 0.002), QRS duration (98 ± 9 vs. 88 ± 7 ms, P <0.001) and incidence of early repolarisation (47% vs. 11%, P = 0.004) were greater in males. Heart rate (57 ± 9 vs. 63 ± 11 bpm P = 0.016) and QTc interval (391 ± 20 vs. 414 ± 17 ms, P <0.001) were greater in females. There was a significant negative correlation between weekly training hours and QTc interval (rs = −0.355, P = 0.009) only. In conclusion, there are significant sex-related ECG differences within RFL athletes that partially mirror previous research. These findings emphasise the importance of considering sex-related variations, during cardiac screening on RFL athletes and enhance our understanding of the normal RFL athlete ECG.